PENGARUH KUALITAS PRODUK ARRUM HAJI PEGADAIAN CABANG PROBOLINGGO TERHADAP MINAT MASYARAKAT UNTUK MENDAFTAR HAJI - Rosyida Apriliya Mardiana; Fathullah Rusly; Nailin Nikmatul Maulidiyah (Universitas Islam Negeri Mataram, 2023)
This study aims to determine the effect of product quality on the Probolinggo branch of Arrum Haji pawnshops on public interest in registering for hajj. The research was conducted with a quantitative approach using descriptive methods. In this study, the population was all customers of the Probolinggo branch of Pegadaian, users of Arrum Haji products during August - October 2022, totaling 46 customers. The data collection technique was carried out using a Likert scale questionnaire. Arrum Hajj Products at the Probolinggo Pawnshop Branch Against Public Interest to Register for Hajj by 78.4%. the calculated t value of the product quality variable (X) is 12.646 with a probability significancy of 0.00 (0.00 < 0.05), then Ho is rejected and Ha is accepted, so it can be concluded that the product quality variable has a positive and significant effect on public interest.